Early Land Plants Today: Index of Liverworts & Hornworts 2013–2014 - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2016)
A widely accessible list of known plant species is a fundamental requirement for plant conservation and has vast applications. An index of published names of liverworts and hornworts between 2013 and 2014 is provided as part of a continued effort in working toward producing a world checklist of this group. The list includes 50 higher taxa, 361 species, 82 infraspecific taxa, and 50 infraspecific autonyms for 2013 and 2014. Three of them are fossils. Five older names not included in the earlier indices are included. Three illegitimate and 13 invalid names are also included.  New to science are 105 species and 22 infraspecific taxa.